2014
DOI: 10.1021/bi5002932
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Stereospecific Interaction of Amphidinol 3 with Sterol in Lipid Bilayers

Abstract: Amphidinol 3 (AM3), a polyhydroxy-polyene metabolite from the dinoflagellate Amphidinium klebsii, possesses potent antifungal activity. Although AM3 permeabilizes phospholipid membranes only in the presence of sterol, the detailed molecular basis by which AM3 recognizes sterols in membranes remains unknown. Here, we investigated the molecular interaction between sterols and AM3 in membranes from the viewpoint of stereospecific molecular recognition using ergosterol, cholesterol, and epicholesterol, which is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…For 4,pore formation was only seen when 3b-OH sterols were present in the membrane and not in the presence of 3a-OH sterols such as epicholesterol. [14] HSQC overlay studies were conducted to provide further insight into the sterol-binding interactions of the karlotoxins. By using aseries of increasing ratios of cholesterol added to 2, HSQC NMR experiments were conducted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For 4,pore formation was only seen when 3b-OH sterols were present in the membrane and not in the presence of 3a-OH sterols such as epicholesterol. [14] HSQC overlay studies were conducted to provide further insight into the sterol-binding interactions of the karlotoxins. By using aseries of increasing ratios of cholesterol added to 2, HSQC NMR experiments were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…The only physical effects noted were reversible anorexia and a single case of necrotizing pancreatitis. [15] …”
mentioning
confidence: 99%
“…We have reported that AM3 adopts a hairpin‐like conformation with a relatively rigid turn structure near the center including the tetrahydropyran rings . Based on these findings obtained from NMR results, a structural model of AM3 in the membrane was proposed (Figure c) . As described above, the turn region, which is conserved among other amphidinols, recognizes the 3β‐OH group of sterols via hydrogen bonds.…”
Section: Membrane‐active Natural Products and Their Interactions Withmentioning
confidence: 70%
“…Measurements of the 1 H NMR T 1M values of AM3 in bicelles containing Mn 2+ , which revealed how far apart the 1 H position was from the membrane surface, showed deeper insertion of the olefinic terminus into the membrane interior, suggesting the predominance of an extended conformation for the hydrophobic polyene portion. We have reported that AM3 adopts a hairpin‐like conformation with a relatively rigid turn structure near the center including the tetrahydropyran rings . Based on these findings obtained from NMR results, a structural model of AM3 in the membrane was proposed (Figure c) .…”
Section: Membrane‐active Natural Products and Their Interactions Withmentioning
confidence: 78%
“…For instance, the amphidinols exhibit antifungal, cytotoxic, hemolytic and anti-diatom activity, in which AM3 ( 1 ) exhibits the most potent antifungal activity (MEC = 4–9 μg per disk against Aspergillus niger ), albeit with hemolytic action (EC 50 = 0.009–0.4 μM against human erythrocyte cells). Interestingly, the mechanism of action for this agent has recently been attributed to its ability to form barrel-stave pores, similar to amphotericin B, which is induced by the stereospecific molecular recognition of membrane sterols 2,3. Specifically, the bis -tetrahydropyran core, which is highly conserved in this family, hydrogen bonds with the 3β-OH of ergosterol and cholesterol to permit the permeabilization of the membrane.…”
Section: Introductionmentioning
confidence: 99%